2014
DOI: 10.1155/2014/858237
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Trypsin Inhibitor Ameliorates Seawater Immersion-Induced Intestinal Mucosa Injury via Antioxidation, Modulation of NF-κB Activity, and Its Related Cytokines in Rats with Open Abdominal Injury

Abstract: Objective. To investigate the role of oxidative stress, NF-κB activity, and its related cytokines in the pathogenesis of seawater immersion after open abdominal injury (SI-OAI) and whether UTI treatment can attenuate SI-OAI induced IMI. Methods. Wistar rats were randomly divided into three groups: C group, S group, and U group. The rats in C group only suffered from anesthesia and surgical operation, whereas the rats in S group and U group received caudal vein injection of normal saline without/with 50,000 U/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The mammalian NF-κB family consists of five members, including RelA (also named p65), RelB, c-Rel, NF-κB1 p50, and NF-κB2 p52, all of which form homo- or hetero-dimers in the cytoplasm. [ 20 ] NF-κB proteins are normally bound to inhibitory molecules of the IκB family of proteins as an inactive complex. Inflammatory cytokines, such as IL-1β and TNFα, can activate the canonical NF-κB pathway, start the phosphorylation and degradation of the IκB protein, particularly IκBα, and cause the onset of NF-κB translocation to the nucleus and target gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian NF-κB family consists of five members, including RelA (also named p65), RelB, c-Rel, NF-κB1 p50, and NF-κB2 p52, all of which form homo- or hetero-dimers in the cytoplasm. [ 20 ] NF-κB proteins are normally bound to inhibitory molecules of the IκB family of proteins as an inactive complex. Inflammatory cytokines, such as IL-1β and TNFα, can activate the canonical NF-κB pathway, start the phosphorylation and degradation of the IκB protein, particularly IκBα, and cause the onset of NF-κB translocation to the nucleus and target gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study in our group has shown that hydrogen gas inhalation attenuates seawater instillation-induced ADLI in rabbits and that the protective effects observed may be related to the activation of the Nuclear factor erythroid 2-related factor 2 (Nrf2) pathway [4]. Additionally, the release of reactive oxygen species and increased cell apoptosis stimulated by seawater instillation were possible mechanisms of lung injury [5,6].…”
Section: Introductionmentioning
confidence: 91%
“…A 6 cm x 6cm gauze was put into 99℃ boiling water for ten seconds, and then was used to prepare 10% of rats °burn of rat [9][10] . Abdominal injury was made by opening the abdomen of the middle of the abdomen, the incision length is 3 cm located under the xiphoid [11] . After the process the rat is stable for about ve minutes, rats in SI group were immersed in 15℃ arti cial seawater for one hour, the waterline is at the level of the xiphoid process,for maintaining its normal breathing.In the Ctl group, except no immersing in seawater, the other treatment methods were the same.…”
Section: Animal Modelsmentioning
confidence: 99%